2018
DOI: 10.3390/medicines5040112
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antifungal, Antibiofilm, and Cytotoxic Activities of Mentha spp. Essential Oils

Abstract: Since ancient times, plants have been used to preserve food, or for their health properties. Essential oils are complex mixtures of volatile compounds that are obtained from botanical material, specifically from aromatic plants. Lamiaceae is one of the most important families in the production of essential oils, as it has both antioxidant and antimicrobial properties. The essential oils of Mentha (the Lamiaceae family) have been extensively studied for their biological actions. In this review, we report the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 90 publications
1
51
0
4
Order By: Relevance
“…With the aim of developing novel antitumor drugs, various EOs have shown high efficacy against human cancer cells and low toxicity to normal human cells. Some EO components, such as terpenes, have been found to be effective against a broad range of cancers, for example, geraniol, D-limonene, and other monoterpenes [35]. Our results indicated that the EO of B. morelensis could be used in topical application for wound because, at a concentration of 1.2 mg/mL, only 24% of peritoneal macrophages were inhibited, in comparison with doxorubicin, and the IC 50 was = 0.85 µg/mL, confirming that EO at the concentration tested was not cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of developing novel antitumor drugs, various EOs have shown high efficacy against human cancer cells and low toxicity to normal human cells. Some EO components, such as terpenes, have been found to be effective against a broad range of cancers, for example, geraniol, D-limonene, and other monoterpenes [35]. Our results indicated that the EO of B. morelensis could be used in topical application for wound because, at a concentration of 1.2 mg/mL, only 24% of peritoneal macrophages were inhibited, in comparison with doxorubicin, and the IC 50 was = 0.85 µg/mL, confirming that EO at the concentration tested was not cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The escalation in the EO content of M. arvensis at 20 mg kg −1 Ni might be due to alterations in the morphology and number of trichomes on plant leaves. Trichomes are the epidermal hairs that helps in plant defence besides producing various chemicals of pharmaceutical importance like EO (Sharma et al 2003), and the EO is stored in secretory compartments like glandular trichomes, cavities and canals (Stringaro et al 2018). Others reported that the content of secondary metabolites in Robinia pseudoacacia L. was improved with the increased concentration of environmental CO 2 in the plants grown under soil polluted with Cd and Pb (Jia et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mentha arvensis, also known as menthol mint, is an aromatic annual herb having pleasant odour leaves and is distributed throughout the western Himalayas. The enormous medicinal uses of the menthol mint including the proliferation of ailments such as bronchitis, nausea, anorexia, liver injury, flatulence, due to its antispasmodic, analgesic, inflammatory, and antiemetic effects, have been well documented in the literature (Cowman 1999;Iscan et al 2002;Moreno et al 2002;Stringaro et al 2018). Uttar Pradesh (UP) is one of the major menthol mint oilproducing states of India.…”
Section: Introductionmentioning
confidence: 99%
“…They are synthesized in the cytoplasm and plastids of plant cells, stored in complex secretory structures like glands or resin conduits, and only then presented as drops in the leaves, stems, flowers, fruits, bark and roots of the plants [170]. EOs are mainly composed of terpenes, terpenoids and phenylpropanoids at the levels of 20%-70% but may also contain fatty acids, oxides and sulfur derivatives [171]. They are generally obtained by steam-or hydro-distillation of plants.…”
Section: Essential Oils (Eos)mentioning
confidence: 99%